Management of Mulai Mookadaipu (nasal polyp) with Manjal Kara applications: A case study - Ganesan, S.; Anpuchelvi, S.; Sritharan, G. (Wolters Kluwer - Medknow, 2025)
The Siddha system of medicine, one of the oldest and most spiritually rooted healing traditions, integrates external therapies and internal medicines for managing health and disease. Nasal polyps, which commonly affect young and older adults, are closely associated with Mulai Mookadaipu in Siddha medicine. This condition is characterized by the abnormal growth of Oon (muscle) and kozhuppu (fatty tissue) within the nasal passages. This case study focuses on a 50-year-old female patient who presented with symptoms of nasal blockage, difficulties in breathing, and anosmia. Clinical examination revealed left maxillary sinus tenderness and nasal polyps in the left nostril, confirmed by a computerized tomography scan. The patient, who had a history of nasal blockage, had previously undergone allopathic treatment but declined the recommended surgical intervention, Instead, she opted for Siddha medicine, where her condition was treated as a chronic nasal polyp using a combination of nasal applications (Nasiyam and Karam Therapy) and internal medicines. The holistic Siddha treatment approach effectively managed the patient’s symptoms, leading to significant improvement in nasal blockage and breathing.
Keywords: Kozhuppu; Manjal kara; Mulai mookadaipu; Oon